French soldiers who died during both World Wars: from recovery to repatriation. (November 2020) - Verna, Emeline; Costedoat, Caroline; Stevanovitch, Alain; Adam, Frédéric; Desfossés, Yves; Jacques, Alain; Signoli, Michel
Highlights: Identification of the remains of French WWI and WWII soldiers is characterized. Legislation affecting the recovery of French soldiers is assessed. The duty to remember recent armed conflicts is discussed. A protocol for the recovery of remains to the identification of a French soldier is outlined. Abstract: The study of human remains from the first and the second World War is important for enhancing our understanding of that historical period. Despite the fact that the period has been well-documented previously, gaps remain, particularly as a result of the destruction of archives. In fact, for just WWI, more than 700, 000 soldiers from both sides remain missing. Scientific and political collaborations established in hopes of recovering and identifying soldiers will allow many families understand "what happened" to their loved ones and facilitate the return of the soldiers their homes. In this paper, the recovery of the human remains of French soldiers WWI and WWII will be described through the lens of the legislation in place governing the retrieval and identification of the remains, protocols established for recovery, excavation and analysis, and the dissemination data. These features will be illustrated using three case studies that involve French soldiers who died during WWI. Research of this type is the result of true interdisciplinary and sometimes international, depending on the context, collaboration. The public and academic the dissemination of these archaeological discoveries, both to academics and the public, is crucial and a type of remembrance.